Annual Plan for 1972-73 Draft Proposals Government of Meghalaya - Planning Commission (Planning Commission, 1972)
The year 1972-73 will be third year or Meghalaya. The State can into being on the End April, 1972 as an autonomous State within the State of Assam. The autonomous State was created as the only experiment of its kind in India trying to meet the aspirations of the fills people. Effort was put forth by all concerned people the people of the Hills and the Government of India this experiment a success. Within a short period in experience has been gained, though it has been emotionally demonstrated that the autonomous status fell very much short hopes and aspiration of the people.
Planning Department Government of Meghalaya